Patterns of ocular morbidity among patients attending leprosy clinic, Siliguri, West Bengal - Rupanjli Lakra; Louis Tirkey (Kerala Journal of Ophthalmology, 2024)
Purpose: To estimate the prevalence and pattern of ocular morbidity among patients attending the leprosy clinic in Siliguri, West Bengal, and identify the risk factors associated with it, if any. Methods: It was a clinic-based observational study with a cross-sectional design conducted at Leprosy Clinic, Siliguri, West Bengal among leprosy patients for 1 year from August 2022 to July 2023. Leprosy patients who had completed multi-drug therapy and consented to the study were enrolled. Convenience sampling was performed and the sample size was 117. After a detailed ophthalmic evaluation, the socio-demographic profile of participants and their ocular morbidities were documented and analyzed. A Chi-square test was performed to identify the factors associated with leprosy complications. P value < 0.05 was considered statistically significant. Results: Overall ocular morbidity for any eye observed was 58.1%. Major findings were cataract (35.9%), aphakia (11.1%), diminished corneal sensation (7.7%), lagophthalmos (7.7%), mild corneal opacity (5.2%), chronic iritis (3.4%), and impaired lid closure (2.6%). Ectropion was present in 2.6% bilaterally. According to the World Health Organization (WHO) criteria for blindness, 11.1% of patients were blind in both eyes. Ocular complications were significantly associated with the respondent’s age, duration of disease, classification of disease, and decreased vision. Conclusions: The present study shows a significant rate of ocular complications and blindness among leprosy patients. Lid abnormalities, corneal abnormalities, and cataracts were the commonly encountered ocular morbidities among treated leprosy patients.